A composite coating and method of making and use thereof

By coating TiC particles with Fe3Al phase and combining it with a specific spraying technique, the problem of weak bonding strength of TiC composite coatings was solved, and high-performance, low-cost composite coating preparation was achieved.

CN118007051BActive Publication Date: 2026-11-06HUNAN METALLURGY MATERIAL RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410012098.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-04
Publication Date
2026-11-06
Estimated Expiration
2044-01-04

AI Technical Summary

Technical Problem

The weak interfacial bonding strength between TiC and the metal substrate leads to poor physical and mechanical properties of the composite coating. Existing processes, such as in-situ synthesis, suffer from problems such as plating solution pollution and low production efficiency.

Method used

A core-shell encapsulation structure is used to encapsulate the Fe3Al phase in TiC particles to form internal crystals. This is combined with supersonic flame spraying, explosive spraying, and cold spraying technologies to prepare a composite coating.

Benefits of technology

It improves the wettability between ceramic particles and the metal substrate, enhances the bonding strength and density of the coating, reduces production costs, and improves the mechanical properties of the coating.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application provides a composite coating and a preparation method and application thereof. The composite coating comprises TiC powder and Fe3Al coating the TiC powder. In the coating, a metal phase is coated on the outer surface of a TiC phase, is combined and dense, is free of pollution at an interface, and endows the coating with excellent mechanical properties. The application also provides a preparation method and application of the composite coating.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functional materials technology, specifically relating to a composite coating, its preparation method, and its application. Background Technology

[0002] TiC possesses excellent physicochemical properties such as high hardness, good thermal stability, oxidation resistance, corrosion resistance, and low density, making it a promising coating material. However, due to the poor wettability and weak bonding force between TiC and metals, the physical and mechanical properties of the composite coating are greatly affected, thus restricting the development of TiC composite coatings.

[0003] Currently, common methods to improve the interfacial bonding strength between TiC and metal substrates include in-situ synthesis and chemical plating. However, these methods suffer from drawbacks such as plating solution contamination, process instability, and low production efficiency, which greatly limit the application and development of TiC composite coatings. Summary of the Invention

[0004] The present invention aims to at least solve one of the aforementioned technical problems existing in the prior art. To this end, the present invention provides a composite coating in which a metallic phase is coated on the outer surface of a TiC phase, the bonding is dense, there is no contamination at the interface, and the coating endows the coating with excellent mechanical properties.

[0005] The present invention also provides a method for preparing a composite coating.

[0006] A first aspect of the present invention provides a composite coating comprising TiC powder and Fe3Al coating the TiC powder.

[0007] One of the technical solutions of the present invention regarding composite coatings has at least the following beneficial effects:

[0008] Fe-Al intermetallic compounds, due to the absence of strategic elements, possess low density, low cost, high strength, good wear resistance, and excellent resistance to oxidation, sulfidation, and carbonization. They are promising anti-wear and high-temperature structural materials with excellent application prospects.

[0009] Due to their long-range ordered structure, Fe3Al intermetallic compounds possess numerous excellent properties. Their corrosion resistance in sulfiding atmospheres is even superior to that of stainless steel and anti-corrosion coatings, making them a potentially practical engineering material that could replace stainless steel and corrosion-resistant alloys in certain applications. Furthermore, Fe3Al intermetallic compounds are thermodynamically compatible with TiC, exhibiting high interfacial bonding strength.

[0010] Therefore, from the perspective of composite material design, composite powder coating materials with ceramic particles as the core and a metal outer layer on the surface possess both the high hardness of ceramic materials and the toughness of metal materials. At the same time, the presence of the metal outer shell significantly improves the wettability between ceramic powder particles, playing a decisive role in obtaining a dense functional coating.

[0011] The composite coating of this invention adopts the principle of core-shell encapsulation, where TiC particles are wrapped by the Fe3Al phase to form internal crystals. This effectively improves the wettability between the ceramic particles and the metal substrate, effectively addresses the performance deficiencies of the TiC composite coating, and results in a composite coating with excellent performance while reducing production costs.

[0012] The composite coating of this invention contains few harmful elements, and the interface between the coating layer and ceramic particles is clean and free of contamination. The TiC particles have a pinning effect on grain boundaries, effectively inhibiting grain boundary migration at high temperatures, thereby refining the grains, stabilizing the Fe3Al grain size, and improving the mechanical properties of the coating.

[0013] The composite coating of the present invention has low oxidation of TiC composite spray powder and can also be used to prepare surface compressive stress coating, improve bonding strength and reduce porosity.

[0014] The composite coating of the present invention has low raw material cost, stable process technology, and significantly improved performance of TiC coating.

[0015] According to some embodiments of the present invention, the particle size of the Fe powder is 2 μm to 3 μm.

[0016] According to some embodiments of the present invention, the particle size of the Al powder is 2 μm to 3 μm.

[0017] According to some embodiments of the present invention, the molar ratio of Fe powder to Al powder is 3:1.

[0018] According to some embodiments of the present invention, the particle size of the TiC powder is 15 μm to 60 μm.

[0019] According to some embodiments of the present invention, the purity of each powder is higher than 99.0%.

[0020] According to some embodiments of the present invention, the thickness of the composite coating is 200 μm to 300 μm.

[0021] A second aspect of the present invention provides a method for preparing a composite coating, comprising the following steps:

[0022] S1: Fe powder and Al powder are mixed and ball-milled for the first time to prepare Fe3Al pre-alloyed powder;

[0023] S2: The Fe3Al pre-alloyed powder and TiC powder are mixed and then ball-milled a second time to obtain Fe3Al-TiC core-shell coated powder;

[0024] S3: After plasma spheroidization treatment, the Fe3Al-TiC core-shell coated powder is coated on the substrate surface to form the composite coating.

[0025] One technical solution of the present invention relating to the preparation method of composite coating has at least the following beneficial effects:

[0026] The preparation method of the present invention does not require expensive equipment and complex process control, the reaction conditions are not harsh, the raw materials are readily available, the production cost is low, and it is easy to industrialize.

[0027] The preparation method of this invention adopts the principle of core-shell coating structure, in which TiC particles are wrapped by Fe3Al phase to form internal crystals. This effectively improves the wettability between ceramic particles and metal matrix, effectively improves the performance deficiencies of TiC composite coatings, and produces composite coatings with excellent performance while reducing production costs.

[0028] The preparation method of this invention uses plasma spheroidization to prepare composite powder, which has fewer harmful elements and a clean and uncontaminated interface between the coating layer and ceramic particles. The TiC particles have a pinning effect on grain boundaries, effectively inhibiting grain boundary migration at high temperatures, thereby refining the grains, stabilizing the Fe3Al grain size, and improving the mechanical properties of the coating.

[0029] The preparation method of the present invention employs supersonic flame spraying, explosive spraying, and cold spraying technologies. Due to the characteristics of its low-temperature and high-speed process technology, it reduces the oxidation of TiC sprayed powder on the one hand, and can also prepare a surface compressive stress coating, improve the bonding strength, and reduce the porosity on the other hand.

[0030] The preparation method of the present invention has low raw material cost, stable process technology, and can significantly improve the performance of TiC coating.

[0031] According to some embodiments of the present invention, the particle size of the Fe powder and Al powder is 2μm to 3μm.

[0032] According to some embodiments of the present invention, the rotational speed of the first ball mill is 400 rpm to 800 rpm.

[0033] According to some embodiments of the present invention, the rotational speed of the first ball mill is 400 rpm to 600 rpm.

[0034] According to some embodiments of the present invention, the rotational speed of the first ball mill is 530 rpm.

[0035] According to some embodiments of the present invention, the ball-to-material ratio of the first ball milling is 15-30:1-3.

[0036] According to some embodiments of the present invention, the ball-to-material ratio of the first ball milling is 30:1.

[0037] According to some embodiments of the present invention, the first ball milling time is 30 min to 40 min.

[0038] According to some embodiments of the present invention, the first ball milling time is approximately 30 minutes.

[0039] According to some embodiments of the present invention, in step S2, the mass fraction of the Fe3Al pre-alloyed powder is 20% to 25%.

[0040] According to some embodiments of the present invention, in step S2, the mass fraction of the Fe3Al pre-alloyed powder is about 23%.

[0041] According to some embodiments of the present invention, the rotational speed of the second ball mill is 300 rpm to 600 rpm.

[0042] According to some embodiments of the present invention, the rotational speed of the second ball mill is 300 rpm to 400 rpm.

[0043] According to some embodiments of the present invention, the rotational speed of the second ball mill is 375 rpm.

[0044] According to some embodiments of the present invention, the ball-to-material ratio of the second ball milling is 12-30:1-3.

[0045] According to some embodiments of the present invention, the ball-to-material ratio of the second ball milling is 10:1.

[0046] According to some embodiments of the present invention, the second ball milling time is 2h to 7h.

[0047] According to some embodiments of the present invention, the second ball milling time is 2h to 5h.

[0048] According to some embodiments of the present invention, the second ball milling time is approximately 3 hours.

[0049] According to some embodiments of the present invention, the power of the plasma spheroidization treatment is 10kW to 20kW.

[0050] According to some embodiments of the present invention, the power of the plasma spheroidization process is 15 kW.

[0051] According to some embodiments of the present invention, the powder feeding rate of the plasma spheroidizing treatment is 5 g / min to 40 g / min.

[0052] According to some embodiments of the present invention, the powder feeding rate of the plasma spheroidization treatment is 30 g / min.

[0053] According to some embodiments of the present invention, the hydrogen flow rate of the plasma spheroidizing treatment is 5 L / min to 8 L / min.

[0054] According to some embodiments of the present invention, the hydrogen flow rate of the plasma spheroidization treatment is 7 L / min.

[0055] According to some embodiments of the present invention, the argon flow rate of the plasma spheroidization treatment is 50 L / min to 70 L / min.

[0056] According to some embodiments of the present invention, the argon flow rate of the plasma spheroidization treatment is 65 L / min.

[0057] According to some embodiments of the present invention, in step S3, the method of coating the substrate surface includes supersonic flame spraying, cold spraying, or explosive spraying.

[0058] High-velocity combustion (HVOF) spraying is a high-speed combustion spraying technology that accelerates fuel gas and powder materials to supersonic speeds and then sprays them at high speed onto the surface of a substrate to form a coating. The coating exhibits high density, low oxygen content, high bonding strength, and low porosity. This spraying technology is suitable for coating hard, wear-resistant, and corrosion-resistant materials and is commonly used to protect industrial parts and surfaces.

[0059] Cold spraying is a high-speed impact spraying technology that accelerates metal powder to supersonic speeds and then impacts the substrate surface at high speed during the spraying process to form a coating. Unlike traditional thermal spraying, cold spraying involves relatively low temperatures, thus avoiding thermal impact on the substrate. It is suitable for temperature-sensitive materials and can form a dense coating with good adhesion. It is commonly used for repairing parts surfaces, applying anti-corrosion coatings, and preparing composite materials.

[0060] Explosive spraying is a technique that uses high-temperature, high-pressure gas generated by an explosive shockwave to propel powder onto the surface of a substrate. The powder is heated, accelerated, and ejected onto the substrate under the impact of the blast wave to form a coating. Explosive spraying can be used to coat materials with high temperature resistance, high hardness, and high wear resistance. One advantage of this method is that it can coat relatively large areas, making it suitable for some special workpieces and materials. Detailed Implementation

[0061] The following are specific embodiments of the present invention, and the technical solutions of the present invention will be further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.

[0062] In some embodiments of the present invention, a composite coating is provided, comprising TiC powder and Fe3Al coated with TiC powder.

[0063] It is understandable that Fe-Al intermetallic compounds, due to the absence of strategic elements, possess low density, low cost, high strength, good wear resistance, and excellent resistance to oxidation, sulfidation, and carbonization, making them promising anti-wear and high-temperature structural materials. Fe3Al intermetallic compounds, with their long-range ordered structure, possess numerous excellent properties; their corrosion resistance in sulfiding atmospheres is even superior to stainless steel and anti-corrosion coatings, making them a potentially practical engineering material that could replace stainless steel and corrosion-resistant alloys in certain applications. Furthermore, Fe3Al intermetallic compounds are thermodynamically compatible with TiC, exhibiting high interfacial bonding strength.

[0064] Therefore, from the perspective of composite material design, composite powder coating materials with ceramic particles as the core and a metal outer layer on the surface possess both the high hardness of ceramic materials and the toughness of metal materials. At the same time, the presence of the metal outer shell significantly improves the wettability between ceramic powder particles, playing a decisive role in obtaining a dense functional coating.

[0065] The composite coating of this invention adopts the principle of core-shell encapsulation, where TiC particles are wrapped by the Fe3Al phase to form internal crystals. This effectively improves the wettability between the ceramic particles and the metal substrate, effectively addresses the performance deficiencies of the TiC composite coating, and results in a composite coating with excellent performance while reducing production costs.

[0066] The composite coating of this invention contains few harmful elements, and the interface between the coating layer and ceramic particles is clean and free of contamination. The TiC particles have a pinning effect on grain boundaries, effectively inhibiting grain boundary migration at high temperatures, thereby refining the grains, stabilizing the Fe3Al grain size, and improving the mechanical properties of the coating.

[0067] The composite coating of the present invention has low oxidation of TiC sprayed powder and can also be used to prepare surface compressive stress coating, improve bonding strength and reduce porosity.

[0068] The composite coating of the present invention has low raw material cost, stable process technology, and significantly improved performance of TiC coating.

[0069] In some embodiments of the present invention, the particle size of the Fe powder is 2 μm to 3 μm.

[0070] In some embodiments of the present invention, the particle size of Al powder is 2 μm to 3 μm.

[0071] In some embodiments of the present invention, the molar ratio of Fe powder to Al powder is 3:1.

[0072] In some embodiments of the present invention, the particle size of TiC powder is 15 μm to 60 μm.

[0073] In some embodiments of the present invention, the purity of each powder is higher than 99.0%.

[0074] In some embodiments of the present invention, the thickness of the composite coating is 200 μm to 300 μm.

[0075] In other embodiments of the present invention, a method for preparing a composite coating is provided, comprising the following steps:

[0076] S1: Fe powder and Al powder are mixed and ball-milled for the first time to prepare Fe3Al pre-alloyed powder;

[0077] S2: Fe3Al pre-alloyed powder and TiC powder are mixed and then ball-milled a second time to obtain Fe3Al-TiC core-shell coated powder;

[0078] S3: Fe3Al-TiC core-shell coated powder is plasma spheroidized and then coated on the substrate surface to form a composite coating.

[0079] It is understood that the preparation method of the present invention does not require expensive equipment and complex process control, the reaction conditions are not harsh, the raw materials are readily available, the production cost is low, and it is easy to industrialize.

[0080] The preparation method of this invention adopts the principle of core-shell coating structure, in which TiC particles are wrapped by Fe3Al phase to form internal crystals. This effectively improves the wettability between ceramic particles and metal matrix, effectively improves the performance deficiencies of TiC composite coatings, and produces composite coatings with excellent performance while reducing production costs.

[0081] The preparation method of this invention uses plasma spheroidization to prepare composite powder, which has fewer harmful elements and a clean and uncontaminated interface between the coating layer and ceramic particles. The TiC particles have a pinning effect on grain boundaries, effectively inhibiting grain boundary migration at high temperatures, thereby refining the grains, stabilizing the Fe3Al grain size, and improving the mechanical properties of the coating.

[0082] The preparation method of the present invention employs supersonic flame spraying, explosive spraying, and cold spraying technologies. Due to the characteristics of its low-temperature and high-speed process technology, it reduces the oxidation of TiC sprayed powder on the one hand, and can also prepare a surface compressive stress coating, improve the bonding strength, and reduce the porosity on the other hand.

[0083] The preparation method of the present invention has low raw material cost, stable process technology, and can significantly improve the performance of TiC coating.

[0084] In some embodiments of the present invention, the particle size of Fe powder and Al powder is 2μm to 3μm.

[0085] In some embodiments of the present invention, the rotation speed of the first ball mill is 400 rpm to 800 rpm.

[0086] In some embodiments of the present invention, the rotation speed of the first ball mill is 400 rpm to 600 rpm.

[0087] In some embodiments of the present invention, the rotation speed of the first ball mill is 530 rpm.

[0088] In some embodiments of the present invention, the ball-to-material ratio in the first ball milling is 15-30:1-3.

[0089] In some embodiments of the present invention, the ball-to-material ratio in the first ball milling is 30:1.

[0090] In some embodiments of the present invention, the first ball milling time is 30 min to 40 min.

[0091] In some embodiments of the present invention, the first ball milling time is about 30 minutes.

[0092] In some embodiments of the present invention, in step S2, the mass fraction of Fe3Al pre-alloyed powder is 20% to 25%.

[0093] In some embodiments of the present invention, in step S2, the mass fraction of Fe3Al pre-alloyed powder is about 23%.

[0094] In some embodiments of the present invention, the rotation speed of the second ball mill is 300 rpm to 600 rpm.

[0095] In some embodiments of the present invention, the rotation speed of the second ball mill is 300 rpm to 400 rpm.

[0096] In some embodiments of the present invention, the rotation speed of the second ball mill is 375 rpm.

[0097] In some embodiments of the present invention, the ball-to-material ratio of the second ball mill is 12-30:1-3.

[0098] In some embodiments of the present invention, the ball-to-material ratio in the second ball mill is 10:1.

[0099] In some embodiments of the present invention, the second ball milling time is 2h to 7h.

[0100] In some embodiments of the present invention, the second ball milling time is 2h to 5h.

[0101] In some embodiments of the present invention, the second ball milling time is about 3 hours.

[0102] In some embodiments of the present invention, the power of plasma spheroidization treatment is 10kW to 20kW.

[0103] In some embodiments of the present invention, the power of the plasma spheroidization process is 15 kW.

[0104] In some embodiments of the present invention, the powder feeding rate for plasma spheroidization treatment is 5 g / min to 40 g / min.

[0105] In some embodiments of the present invention, the powder feeding rate for plasma spheroidization treatment is 30 g / min.

[0106] In some embodiments of the present invention, the hydrogen flow rate for plasma spheroidization is 5 L / min to 8 L / min.

[0107] In some embodiments of the present invention, the hydrogen flow rate for plasma spheroidization is 7 L / min.

[0108] In some embodiments of the present invention, the argon flow rate for plasma spheroidization is 50 L / min to 70 L / min.

[0109] In some embodiments of the present invention, the argon flow rate for plasma spheroidization is 65 L / min.

[0110] In some embodiments of the present invention, the method of coating the substrate surface in step S3 includes supersonic flame spraying, cold spraying, or explosive spraying.

[0111] High-velocity combustion (HVOF) spraying is a high-speed combustion spraying technology that accelerates fuel gas and powder materials to supersonic speeds and then sprays them at high speed onto the surface of a substrate to form a coating. The coating exhibits high density, low oxygen content, high bonding strength, and low porosity. This spraying technology is suitable for coating hard, wear-resistant, and corrosion-resistant materials and is commonly used to protect industrial parts and surfaces.

[0112] Cold spraying is a high-speed impact spraying technology that accelerates metal powder to supersonic speeds and then impacts the substrate surface at high speed during the spraying process to form a coating. Unlike traditional thermal spraying, cold spraying involves relatively low temperatures, thus avoiding thermal impact on the substrate. It is suitable for temperature-sensitive materials and can form a dense coating with good adhesion. It is commonly used for repairing parts surfaces, applying anti-corrosion coatings, and preparing composite materials.

[0113] Explosive spraying is a technique that uses high-temperature, high-pressure gas generated by an explosive shockwave to propel powder onto the surface of a substrate. The powder is heated, accelerated, and ejected onto the substrate under the impact of the blast wave to form a coating. Explosive spraying can be used to coat materials with high temperature resistance, high hardness, and high wear resistance. One advantage of this method is that it can coat relatively large areas, making it suitable for some special workpieces and materials.

[0114] The technical solution of the present invention will be better understood below with reference to specific embodiments.

[0115] It should be noted that all reagents used in the examples were obtained from commercially available sources.

[0116] Example 1

[0117] A composite coating was prepared, and the specific process is as follows:

[0118] According to the composition design requirements, Fe powder and Al powder were weighed and mixed, with the molar ratio of Fe powder to Al powder being 3:1, to prepare Fe3Al pre-alloyed mixed powder.

[0119] The prepared mixed powder was placed in a sealed container of a high-energy ball mill, and the mixture was evacuated under an argon atmosphere for 30 minutes. The ball-to-powder ratio was 30:1, and the ball mill speed was 530 rpm.

[0120] Fe3Al pre-alloyed powder and TiC powder were mixed and placed in a ball mill. The mass fraction of Fe3Al pre-alloyed powder was 23 wt.%. The mixture was ball-milled for 3 hours with a ball-to-material ratio of 10:1 and a ball mill speed of 375 rpm.

[0121] The prepared Fe3Al-TiC core-shell coated powder was subjected to plasma spheroidization treatment with a plasma power of 15kW, a feed rate of 30g / min, a hydrogen flow rate of 7L / min, and an argon flow rate of 65L / min to obtain Fe3Al-TiC composite powder.

[0122] The prepared composite powder was used to prepare a TiC composite coating using a supersonic spraying device.

[0123] Example 2

[0124] A composite coating was prepared, and the specific process is as follows:

[0125] According to the composition design requirements, Fe powder and Al powder were weighed and mixed, with the molar ratio of Fe powder to Al powder being 3:1, to prepare Fe3Al pre-alloyed mixed powder.

[0126] The prepared mixed powder was placed in a sealed container of a high-energy ball mill, and the mixture was evacuated under an argon atmosphere for 30 minutes. The ball-to-powder ratio was 30:1, and the ball mill speed was 530 rpm.

[0127] Fe3Al pre-alloyed powder and TiC powder were mixed and placed in a ball mill. The mass fraction of Fe3Al pre-alloyed powder was 23 wt.%. The mixture was ball-milled for 3 hours with a ball-to-material ratio of 10:1 and a ball mill speed of 375 rpm.

[0128] The prepared Fe3Al-TiC core-shell coated powder was subjected to plasma spheroidization treatment with a plasma power of 15kW, a feed rate of 30g / min, a hydrogen flow rate of 7L / min, and an argon flow rate of 65L / min to obtain Fe3Al-TiC composite powder.

[0129] The prepared composite powder was used to prepare a TiC composite coating using an explosive spraying device.

[0130] Example 3

[0131] A composite coating was prepared, and the specific process is as follows:

[0132] According to the composition design requirements, Fe powder and Al powder were weighed and mixed, with the molar ratio of Fe powder to Al powder being 3:1, to prepare Fe3Al pre-alloyed mixed powder.

[0133] The prepared mixed powder was placed in a sealed container of a high-energy ball mill, and the mixture was evacuated under an argon atmosphere for 30 minutes. The ball-to-powder ratio was 30:1, and the ball mill speed was 530 rpm.

[0134] Fe3Al pre-alloyed powder and TiC powder were mixed and placed in a ball mill. The mass fraction of Fe3Al pre-alloyed powder was 23 wt.%. The mixture was ball-milled for 3 hours with a ball-to-material ratio of 10:1 and a ball mill speed of 375 rpm.

[0135] The prepared Fe3Al-TiC core-shell coated powder was subjected to plasma spheroidization treatment with a plasma power of 15kW, a feed rate of 30g / min, a hydrogen flow rate of 7L / min, and an argon flow rate of 65L / min to obtain Fe3Al-TiC composite powder.

[0136] The prepared composite powder was used to prepare a TiC composite coating using a cold spraying device.

[0137] Comparative Example 1

[0138] A composite coating was prepared, and the specific process is as follows:

[0139] According to the composition design requirements, Fe3Al powder and TiC powder were weighed and mixed to prepare Fe3Al-TiC mixed powder.

[0140] The prepared mixed powder was placed in a sealed container of a ball mill, and the mixture was evacuated under an argon atmosphere and milled for 3 hours. The ball-to-powder ratio was 10:1, and the ball mill speed was 375 rpm.

[0141] The prepared composite powder was used to prepare a TiC composite coating using a JP-8000 supersonic spraying equipment.

[0142] Comparative Example 2

[0143] A composite coating was prepared, and the specific process is as follows:

[0144] According to the composition design requirements, Fe3Al powder and TiC powder were weighed and mixed to prepare Fe3Al-TiC mixed powder.

[0145] The prepared mixed powder was placed in a sealed container of a ball mill, and the mixture was evacuated under an argon atmosphere and milled for 3 hours. The ball-to-powder ratio was 10:1, and the ball mill speed was 375 rpm.

[0146] The prepared composite powder was used to prepare a TiC composite coating using an explosive spraying device.

[0147] Comparative Example 3

[0148] A composite coating was prepared, and the specific process is as follows:

[0149] According to the composition design requirements, Fe3Al powder and TiC powder were weighed and mixed to prepare Fe3Al-TiC mixed powder.

[0150] The prepared mixed powder was placed in a sealed container of a ball mill, and the mixture was evacuated under an argon atmosphere and milled for 3 hours. The ball-to-powder ratio was 10:1, and the ball mill speed was 375 rpm.

[0151] The prepared composite powder was used to prepare a TiC composite coating using a cold spraying device.

[0152] Detection example

[0153] According to the formulations of Examples 1-3 and Comparative Examples 1-3, composite coatings with corresponding numbers were prepared, and the microhardness of these composite coatings was measured. The measurement results are shown in Table 1.

[0154] Table 1 Performance of Composite Coating

[0155] serial number Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Hardness / HV 1286 1135 1178 863 786 795

[0156] As shown in Table 1, the TiC composite coatings prepared using the formulation of this invention, corresponding to the samples numbered 1-3 in Examples, show the following differences compared to Comparative Examples 1-3:

[0157] The core-shell coating method used in this invention, combined with the plasma spheroidization process to prepare composite coating materials, under the same process conditions, significantly improves the hardness and mechanical properties of the composite coating compared to the mechanically mixed Comparative Examples 1-3, such as Example 1 and Comparative Example 1, Example 2 and Comparative Example 2, Example 3 and Comparative Example 3.

[0158] The test results of Examples 1 to 3 show that the composite coating of the present invention is applicable to different spraying processes and the prepared coating has stable performance, indicating that the coating effect is good and can play an excellent role in a variety of situations.

[0159] Comparative Examples 1 to 3 used mechanically mixed powders, without creating a core-shell structure; they were simply mechanically mixed to form a mixed powder. As shown in Table 1, the TiC composite coating process prepared in this invention, compared to the mechanical mixing method, not only improves the compatibility between the ceramic phase powder particles and the base metal, but also enhances the physicochemical properties of the coating material and improves the mechanical properties of the coating.

[0160] The present invention has been described in detail above with reference to the embodiments. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention.

Claims

1. A composite coating, characterized in that, The composite coating comprises TiC powder and Fe3Al coating the TiC powder; the composite coating is prepared by a method comprising the following steps: S1: Fe powder and Al powder are mixed and ball-milled for the first time to prepare Fe3Al pre-alloyed powder, wherein the molar ratio of Fe powder to Al powder is 3:1; S2: The Fe3Al pre-alloyed powder and TiC powder are mixed and then ball-milled a second time to obtain Fe3Al-TiC core-shell coated powder. The mass fraction of the Fe3Al pre-alloyed powder is 20%~25%, and the particle size of the TiC powder is 15μm~60μm. S3: After plasma spheroidization treatment of the Fe3Al-TiC core-shell coated powder, it is coated on the substrate surface to form the composite coating.

2. The composite coating according to claim 1, characterized in that, The thickness of the composite coating is 200μm~300μm.

3. The composite coating according to claim 1, characterized in that, The particle size of the Fe powder and Al powder is 2μm~3μm.

4. The composite coating according to claim 1, characterized in that, The rotation speed of the first ball mill is 400 rpm to 800 rpm; and / or, the ball-to-material ratio of the first ball mill is 15 to 30: 1 to 3; and / or, the time of the first ball mill is 30 min to 40 min.

5. The composite coating according to claim 1, characterized in that, The rotation speed of the second ball mill is 300 rpm to 600 rpm; and / or, the ball-to-material ratio of the second ball mill is 12 to 30: 1 to 3; and / or, the time of the second ball mill is 2 hours to 7 hours.

6. The composite coating according to claim 1, characterized in that, The power of the plasma spheroidizing treatment is 10kW~20kW; and / or, the powder feeding rate of the plasma spheroidizing treatment is 5g / min~40g / min; and / or, the hydrogen flow rate of the plasma spheroidizing treatment is 5L / min~8L / min; and / or, the argon flow rate of the plasma spheroidizing treatment is 50L / min~70L / min.

7. The composite coating according to claim 1, characterized in that, In step S3, the coating method on the substrate surface includes supersonic flame spraying, cold spraying, or explosive spraying.